Effect of kenaf fibre as reinforcing fillers in corn starch-based biocomposite film - Hazrol, M. D.; M. Sapuan, S.; Zainudin, E. S.; A. Wahab, N. I.; A. Ilyas, R. (MDPI, 2022)
Biocomposite films were prepared using corn starch (CS), sorbitol as a plasticiser, and multi-scale kenaf fibre as reinforcing filler. The microstructure and the physical, tensile, and water barrier properties of corn starch reinforced with kenaf fibre were characterised and investigated. The biocomposite films were developed via the solution casting technique using 10 g of CS with 0 to 8% kenaf fibre as filler treated with 30% (w/w, starch basis) of sorbitol. The increased amount of kenaf fibre introduced contributed to improvements in film thickness, weight, and density. Conversely, slight reductions in the biocomposite films’ moisture content, water absorption, and solubility rating were 9.86–5.88%, 163.13–114.68%, and 38.98–25.17%, respectively. An X-ray diffraction (XRD) test revealed that the films were amorphous and that there was no effect on the crystallinity structure of films with kenaf fibre reinforcement. Fourier transform infrared (FT-IR) and rheological analysis indicated that kenaf fibre could weaken the molecular interaction of the film matrix. Field emission scanning electron microscope (FESEM) revealed the arrangement and uniform distribution of kenaf fibre at 0.2–0.8%. The incorporation of kenaf increased the tensile strength, Young’s modulus, and elongation at break until (6% wt) of fibre. With the kenaf fibre incorporation, the optimal tensile strength, Young’s modulus, and elongation at break of the films reached 17.74 MPa, 1324.74 MPa, and 48.79%, respectively. Overall, the introduction of kenaf fibre as filler enhanced the physical and mechanical properties of CS films.